2011
DOI: 10.1016/j.artmed.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of redundant semantic type assignments for organic chemicals in the UMLS

Abstract: Objective The Unified Medical Language System (UMLS) integrates terms from different sources into concepts and supplements these with the assignment of one or more high-level semantic types (STs) from its Semantic Network (SN). For a composite organic chemical concept, multiple assignments of organic chemical STs often serve to enumerate the types of the composite’s underlying chemical constituents. This practice sometimes leads to the introduction of a forbidden redundant ST assignment, where both an ST and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is a challenge to automate such a process, except for cases when well-defined rules are violated. As examples of such errors and their QA see studies of “an algorithm for detecting redundant ST assignment for UMLS concepts” [36] and “redundant ST assignments for organic chemicals” [32]. The error of Semantic Inversion [34] in this paper, also falls into this category.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is a challenge to automate such a process, except for cases when well-defined rules are violated. As examples of such errors and their QA see studies of “an algorithm for detecting redundant ST assignment for UMLS concepts” [36] and “redundant ST assignments for organic chemicals” [32]. The error of Semantic Inversion [34] in this paper, also falls into this category.…”
Section: Discussionmentioning
confidence: 94%
“…These cases are common in the UMLS, especially for chemicals. Our previous research on combinations of STs is embodied in the Refined Semantic Network [2332]. Further, for a study of disjunctive and conjunctive concepts in terminologies see work by Mendonca et al [33].…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al 47 modified RSN to model chemical concepts with multiple “Chemical Viewed Structurally” STs, identifying concepts with an invalid combination of STs and with incorrect ST assignments. Morrey et al 75 resolved redundant ST assignments for chemical composites with multiple STs based on the relative sizes of components in the molecular structure of a composite. A Chemical Specialty Semantic Network 76 was developed to provide a better categorization of chemical concepts in the UMLS.…”
Section: Resultsmentioning
confidence: 99%
“…In Gu et al, 45 , 71 2 refinements were presented. In Chen et al 47 and Morrey et al, 75 , 76 special modeling was required for chemical concepts and ISTs in which intersections are frequent. Then, in He et al, 21 a longitudinal study showed that, while NLM corrected reported errors, eliminating nonsensical or forbidden ISTs (by SN use notes), those ISTs pop up again after a year or 2.…”
Section: Discussionmentioning
confidence: 99%
“…Significant time and effort has gone into cross-referencing semantically equivalent entities across the ontologies, and new terms and alignments continue to be added as the field develops. These manual alignments are high quality, but considered to be incomplete (Morrey et al, 2011;Mougin and Grabar, 2014).…”
Section: Deriving Training Data From Umlsmentioning
confidence: 99%